Legal Analysis of the Violation of the Principle of Objective Selection in Public Consulting Contracts of Minimal Amount - Jaimes Fernández, Elías (2024)
State contracting in Colombia is a fundamental tool for the state to fulfill its objectives and guarantee the protection of citizens' rights. This study analyzes the infringement of the principle of objective selection of consulting contracts under the modality of minimum quantity selection where the criterion of lowest price prevails over other factors such as experience and technical capacity.The principles governing state contracting will be examined, with transparency, economy, responsibility and objective selection as in line with article 209 of the Political Constitution. The analysis focuses on the normative and practical conflicts that arise when applying the selection criteria in this modality as especially found with other forms of contracting such as the merit-based competition.The study concludes that selection based exclusively on the lowest price may violate the principle of objective selection and compromise the choice of proposals that truly satisfy collective interests. This critical analysis provides legal recommendations to strengthen the effectiveness of contracting processes and ensure compliance with the constitutional and regulatory principles that guide the administrative function in Colombia.
Keywords: Government contracting; Objective selection; Minimum quantity; Constitutional principles; Consulting